2018
DOI: 10.18632/oncotarget.25316
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic acid induces p53-dependent apoptosis via the ERK/JNK/AKT pathway in cancer cell lines in prostatic cancer xenografts in mice

Abstract: We evaluated oleanolic acid (OA)-induced anti-cancer activity, apoptotic mechanism, cell cycle status, and MAPK kinase signaling in DU145 (prostate cancer), MCF-7 (breast cancer), U87 (human glioblastoma), normal murine liver cell (BNL CL.2) and human foreskin fibroblast cell lines (Hs 68). The IC50 values for OA-induced cytotoxicity were 112.57 in DU145, 132.29 in MCF-7, and 163.60 in U87 cells, respectively. OA did not exhibit toxicity in BNL CL. 2 and Hs 68 cell lines in our experiments. OA, at 100 µg/mL, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 54 publications
1
34
0
Order By: Relevance
“…1), a pentacyclic triterpenoid widely found in plants, whose cytotoxic effect has been tested in numerous tumor cell lines, such as lung cancer (3), breast cancer (4), colon cancer (5) and melanoma cell lines (6), is considered a promising anticancer drug. Insights have been gained with regard to the complexity of mechanisms underlying the antitumor effect of OA, as follows: i) induction of an increased expression of p53 tumor protein, cytochrome c, caspase-3 apoptosis-promoting protein and Bax; ii) triggering of mitochondrial mediated apoptosis; iii) inhibition of Akt, mTOR and S6K protein expression; iv) cell cycle arrest in different phases in a cancer type-depen-Mechanistic investigations of antitumor activity of a Rhodamine B-oleanolic acid derivative bioconjugate dent manner by altering the expression of regulatory cell cycle proteins (7)(8)(9); v) antioxidant activity by exerting scavenging effect against superoxide anion, hydroxyl radical, nitric oxide and hydrogen peroxide and also by increasing the ferrous iron chelating activity (10); and vi) inhibition of angiogenesis in a dose-dependent manner (11).…”
Section: Introductionmentioning
confidence: 99%
“…1), a pentacyclic triterpenoid widely found in plants, whose cytotoxic effect has been tested in numerous tumor cell lines, such as lung cancer (3), breast cancer (4), colon cancer (5) and melanoma cell lines (6), is considered a promising anticancer drug. Insights have been gained with regard to the complexity of mechanisms underlying the antitumor effect of OA, as follows: i) induction of an increased expression of p53 tumor protein, cytochrome c, caspase-3 apoptosis-promoting protein and Bax; ii) triggering of mitochondrial mediated apoptosis; iii) inhibition of Akt, mTOR and S6K protein expression; iv) cell cycle arrest in different phases in a cancer type-depen-Mechanistic investigations of antitumor activity of a Rhodamine B-oleanolic acid derivative bioconjugate dent manner by altering the expression of regulatory cell cycle proteins (7)(8)(9); v) antioxidant activity by exerting scavenging effect against superoxide anion, hydroxyl radical, nitric oxide and hydrogen peroxide and also by increasing the ferrous iron chelating activity (10); and vi) inhibition of angiogenesis in a dose-dependent manner (11).…”
Section: Introductionmentioning
confidence: 99%
“…As revealed in Figure 7, OA increases the apoptosis through Bad overexpression by suppressing the mTOR pathway activation via AMPK pathway,11 which inhibits mTOR phosphorylation to suppress protein synthesis in cancer cells 55. OA also significantly enhances the antitumor activity via p53-induced caspase-mediated pro-apoptotic signaling pathway 56. As shown in Figure 7, p53 pathway proapoptotic proteins, such as p53, Bax, cytochrome C, and caspase-3 were upregulated, while the anti-apoptotic Bcl-2 expression was decreased.…”
Section: Resultsmentioning
confidence: 97%
“…Cell cycle analysis revealed that oleanolic acid induced cell cycle arrest in HepG2 cells at the sub-G1 (apoptotic) phase of the cell cycle, in a dose-dependent manner [39]. Kim et al [59] showed that the compound increased apoptosis and decreased cell cycling in xenotransplanted prostate DU145 cells. Activation of the genes p53, Bax, and Akt was observed, while cyclin B1, cyclin E, cdk2, p -erk, and c-jun activities were down-regulated.…”
Section: Bioactive Compounds In Beetrootmentioning
confidence: 99%